2017
DOI: 10.1097/mpg.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Pediatric Inflammatory Bowel Disease

Abstract: The trend towards decriminalization of cannabis (marijuana) continues sweeping across the United States. Colorado has been a leader of legalization of medical and recreational cannabis use. The growing public interest in the medicinal properties of cannabis and its use by patients with a variety of illnesses including inflammatory bowel disease (IBD) makes it important for pediatric gastroenterologists to understand this movement and its potential impact on patients. This article describes the path to legaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…6 As of March 2017, 28 states and Washington DC have legalised cannabis for medical purposes, and limited observational studies have demonstrated that medical marijuana, through interaction with the endogenous cannabinoid system [ECS], can potentially be used to alleviate a number of IBDassociated intestinal symptoms including reducing nausea, stool frequency, and abdominal pain, while improving appetite and weight gain. 7 However, it is unclear if the symptomatic relief experienced by patients using cannabis in IBD is accompanied by improvement of intestinal inflammation or any real disease-modifying effect. 8 Indeed, one such study showed that the patients with Crohn's disease who used cannabis had worse disease prognosis and higher tendency toward surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…6 As of March 2017, 28 states and Washington DC have legalised cannabis for medical purposes, and limited observational studies have demonstrated that medical marijuana, through interaction with the endogenous cannabinoid system [ECS], can potentially be used to alleviate a number of IBDassociated intestinal symptoms including reducing nausea, stool frequency, and abdominal pain, while improving appetite and weight gain. 7 However, it is unclear if the symptomatic relief experienced by patients using cannabis in IBD is accompanied by improvement of intestinal inflammation or any real disease-modifying effect. 8 Indeed, one such study showed that the patients with Crohn's disease who used cannabis had worse disease prognosis and higher tendency toward surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…34 However, human subject research involving cannabis remains uniquely challenging because cannabis is a schedule 1 drug under federal law. 3 Route of use of marijuana by participants with IBD may also be a factor in efficacy and safety. The majority in our study smoke marijuana, like most surveys.…”
Section: Discussionmentioning
confidence: 99%
“…2 Patients and families have advocated using marijuana for the treatment of medical conditions and ask care providers about it for treating their IBD. 3,4 Emerging understanding of the endocannabinoid system provides a rationale for considering the medical benefits of marijuana. 5 In addition to reducing pain, there may be effects on nausea, vomiting, gastrointestinal tract motility, and inflammation.…”
mentioning
confidence: 99%
“…O THC age como um agonista fraco do receptor CB1 e, por meio dessa via, também pode interromper a proliferação de células T, as mesmas células Th1 pró-inflamatórias que produzem IFNγ e estão fortemente envolvidas na patogênese da DII. O THC eleva as concentrações das citocinas IL-10 e TGFβ, responsáveis por regular as células T. Assim, o THC ao diminuir a proliferação de células T pode melhorar a regulação dessa função (Hoffenberg et al, 2017).…”
Section: Efeitos Sobre O Trato Gastrointestinalunclassified